Exploring Plurilingualism as a Phenomenon, as a Lens, and as a Pedagogy: A Literature Study - Emma L. Villacorta (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
This article provides a comprehensive literature review of plurilingualism, focusing on its origin, as theoretical framework, and applications in a language instruction. By examining previous and recent studies, this paper highlights the evolving trends in plurilingualism such as a phenomenon, as a lens, and plurilingualism as pedagogy. The findings underscore the importance of plurilingualism which is an emerging approach to language instruction in multicultural country which caters students with multiple visa. This study concludes with recommendations for future research directions in plurilingualism.